PEMBERIAN VAKSINASI BOOSTER COVID-19 SEBAGAI UPAYA PERCEPATAN TERBENTUKNYA KEKEBALAN KELOMPOK PADA MASYARAKAT DI WILAYAH DKI JAKARTA - Evi Susanti Sinaga; Rudy Pou; Gita Handayani Tarigan; Bambang Endro Yuwono; Hartini Hartini (JUARA: Jurnal Wahana Abdimas Sejahtera, 2022)
Currently, the entire population of the world is facing the Covid-19 pandemic. The beginning of this pandemic was known from the first report, an outbreak in the city of Wuhan, China, at the end of December 2019. Data in April 2022, Covid-19 has spread to 230 countries with the number of confirmed cases globally as many as 505,035,185 and 6,210,719 cases died. In Indonesia, confirmed cases of Covid-19 reached 6,042,595 cases, 5,855,361 cases recovered and 156,015 cases died. The three provinces with the highest number of confirmed Covid-19 cases and those who died from Covid-19 were DKI Jakarta, West Java, and Central Java. Vaccination is one of the efforts to overcome the Covid-19 pandemic, where the government is currently very serious about creating herd immunity. This community service provided free booster vaccinations to reduce the spread of Covid-19. The Covid-19 booster vaccination was carried out according to the five-day planned schedule. The community served 1314 (87%) from 1511 registrants, and as many as 20 people (1%) had their vaccine delayed due to health reasons. There was no adverse event following immunisation (AEFI) during the vaccination activities.